전자기파 신호분석을 통한 무기체계 부품 이상행위 탐지 연구 - 고장혁; Janghyuk Kauh; 정창민; Changmin Jeong; 권구형; Koohyung Kwon (Inteonet jeongbo hakoe nonmunji = Journal of Korean Society for Internet Information, 2025)
본 논문은 무기체계 및 IoT 장비 부품에서 발생하는 이상행위를 탐지하기 위해 부채널 분석을 이용하여 장비 부품 해체와 같은 파괴적 방법이 아닌 조립된 상태 그대로 검사하는 비파괴적 방법의 적용 가능성을 보였다. 무기체계 부품에서 발생하는 이상행위는 하드웨어 트로이목마 (HT, Hardware Trojan)에 의해 발생하는 것을 의미하며 부채널 분석 방법 중에서도 전자기파 신호분석을 이용하였다. 초기 시험은 HT공유 포털에서 제공하는 암호 모듈인 AES(Advanced Encryption Standard)-128 GM(Golden Model)과 HT들로 시험했으며 대상 하드웨어 플랫폼은 먼저 FPGA(Field Programmable Gate Array)에서, 그 후에는 ASIC(Application Specific Integrated Circuit) 칩을 제작하여 시험하였다. IoT 장비로는 RC 자동차, 무기체계 장비 부품으로는 군통신체계에 사용된 FPGA와 동일한 신규 제품과 시뮬레이션 장비를 이용하여 시험함으로써 무기체계에서 부품 이상 여부를 탐지할 수 있는 기술의 적용 가능성을 보였다. This paper demonstrates the possibility of a non-destructive method that inspects the assembled state of the equipment circuit rather than a destructive method such as disassembling the equipment circuits, using side-channel analysis to detect abnormal behaviors in weapon systems and IoT equipment circuits. The abnormal behaviors generated in weapon system circuits are caused by hardware Trojans (HTs), and electromagnetic signal analysis was used among the side-channel analysis methods. The initial experiments were conducted with the AES-128 GM, an encryption module provided by the HT sharing portal, and HTs. The target hardware platform was first implemented in the FPGA, and then tested on the manufactured ASIC chip. Initially, the tests were conducted using supervised learning machine learning as an abnormal behavior detection algorithm, and then unsupervised learning deep learning models were used. After proving the possibility with the FPGA and the manufactured ASIC chip, the tests were conducted on the RC car as IoT equipment, and the possibility of the circuit abnormal behavior detection technology was demonstrated by conducting experiments on the same product FPGA applied to the weapon system.